2021
DOI: 10.3389/fpls.2021.713490
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics and Targeted Quantitative Analysis of Temporal and Spatial Variations in Specialized Metabolites Accumulation in Poria cocos (Schw.) Wolf (Fushen)

Abstract: Poria cocos (Schw.) Wolf is a saprophytic fungus that grows around the roots of old, dead pine trees. Fushen, derived from the sclerotium of P. cocos but also containing a young host pine root, has been widely used as a medicine and food in China, Japan, Korea, Southeast Asian countries, and some European countries. However, the compound variations at the different growth periods and in the different parts of Fushen have not previously been investigated. In this study, an untargeted metabolomics approach based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A heat map can directly show intragroup and intergroup similarities and differences, and cluster analysis is a clustering tool to evaluate the difference through an algorithm to produce a dendrogram ( Yang et al, 2021 ). Thus, heatmap cluster analysis with complete linkage after column scaling with normalization was used in this study to evaluate the similarities and differences of different types of Huangjing .…”
Section: Resultsmentioning
confidence: 99%
“…A heat map can directly show intragroup and intergroup similarities and differences, and cluster analysis is a clustering tool to evaluate the difference through an algorithm to produce a dendrogram ( Yang et al, 2021 ). Thus, heatmap cluster analysis with complete linkage after column scaling with normalization was used in this study to evaluate the similarities and differences of different types of Huangjing .…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological studies showed that porcine acid B has a strong anti-inflammatory effect ( Zhang et al, 2021 ). Polyporenic acid C potentiates insulin and induces differentiation of ST-13 preadipocytes ( Yang et al, 2021 ). Based on the above findings, we chose poricoic acid B and polyporenic acid C to determine whether triterpenic acid could alleviate the damage to L-02 hepatocytes in a 5% fatty emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…Wolf has been widely used as a medicine and food in China. An approach based on UHPLC-Q/TOF-MS was utilized to characterize the temporal and spatial variations in the accumulation of specialized metabolites in Fushen, and the quantitative method was successfully applied to simultaneously determine 13 major triterpenoid acids in the nine growth periods and four parts ( Yang M. et al, 2021 ).…”
Section: Application Of Uhplc-hrmsmentioning
confidence: 99%